1985
DOI: 10.1192/bjp.147.3.272
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Long-Term Lithium Outcome

Abstract: The failure rate in long-term lithium treatment of bipolar affective disorder is in the range of 20 to 30%, even with rigorous diagnostic criteria an adequate serum lithium levels. This may be due to a variety of biologic and psychosocial factors. Psychosocial factors affecting treatment outcome were studied in 60 RDC diagnosed bipolar patients treated with lithium for one year. Outcome was measured using an affective episode score, a social adjustment scale and a global assessment scale. Social support was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 22 publications
3
30
0
1
Order By: Relevance
“…Other aspects could be environmental factors, such as social support [9, 31, 32] or life events [33]. Moreover, there are studies showing that the problems and difficulties in functioning experienced by patients with bipolar disorder are closely related to the support provided by different agents and environmental factors, including the family and the community, social services, systems and policies [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other aspects could be environmental factors, such as social support [9, 31, 32] or life events [33]. Moreover, there are studies showing that the problems and difficulties in functioning experienced by patients with bipolar disorder are closely related to the support provided by different agents and environmental factors, including the family and the community, social services, systems and policies [21].…”
Section: Resultsmentioning
confidence: 99%
“…However, a substantial proportion of bipolar patients show persistent subsyndromal symptoms, and most individuals with bipolar disorder are symptomatic more than half of their lives despite receiving pharmacological treatment [3, 4]. Even those patients who achieve full clinical remission show difficulties in making a complete functional recovery, returning to their premorbid level of functioning [5,6,7,8,9,10,11,12,13,14,15,16,17,18]. Nevertheless, psychosocial outcomes in patients with bipolar disorder have generally received less attention than those in patients with psychosis [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 60 BD patients were evaluated, according to the criteria of the third revision of the Diagnostic and Statistical Manual of Mental Disorders (DSM-III), by way of the Personal Resources Inventory (PRI), and the results showed that the use of lithium was related to high rates of social support. The researchers highlighted the importance of psychosocial variables in the course of treatment response, pointing out that social support is a part of confronting mechanisms, which positively influence the patient's prognosis 15 . These data were corroborated in another crosssectional study evaluating 118 BD patients taking lithium, through the Social Support Questionnaire (SSQ), revealing that high rates of social support contributed to a decrease in mania and depression 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low social support may lead to prolonged period of disorder [13,14] and it would increase relapse rate per annum [15,16,17]. Social support maintains synergic role with lithium therapy for this group of patients [18] and would alleviate the relapse risk of depression or mania episodes [19].…”
Section: Introductionmentioning
confidence: 99%